ABFRAKSI DAN PENATALAKSANAANNYA (LAPORAN KASUS) - Nina Novinka; Bambang Nursasongko (Faculty of Dentistry, Universitas Indonesia, 2015)
Abfraction is a cervical non caries lesion which occur mostly as a result of traumatic occlusion, needs to be taken into consideration. The aim of this case study is to understand how to treat abfraction lesion. First the focus of treatment is only to endodontic case but pain was still existed after the root canal treatment and it revealed that there were abfraction lesion on the other 5 teeth. Treatment of those lesions consisted of filling with GIC cement and occlusal adjustment.